Dracula: A Romance - Fairweather, Donald (My University, 1977)
Although there have been a large number of studies done on the subject of vampires which indirectly deal with Bram Stoker's Dracula, there have been very few attempts to examine the novel from a literary perspective. There are a few works which chronicle the appearance of the vampire in literature, but these tend to be essentially anthropological or historical studies. The only extensive literary analysis of the novel is that provided by Leonard Wolf in A Dream of Dracula. Wolf characterizes Dracula as a gothic romance and then proceeds to examine the novel within the tradition of the gothic novel.
While this study deals briefly with the influence of the gothic tradition on Dracula, in essence it is an attempt to examine Dracula within the context of romance literature and the conventions of that tradition as articulated by Northrop Frye. An analysis of the novel is put forward based on Stoker's use of these conventions. Thereaher, the conventions of romance and the analysis of the novel which they suggest are then discussed with re ference to various theories of the psychological significance of romance; most notably the theories of Carl Jung and his disciple, Erich Neumann.
Keywords: English Language and Literature; English Language and Literature